Lean Accounting in Transforming the Organizational Culture in PT. A - Sugianto W, Andreas; Pontjoharyo, Wiyono (IJRDO - Journal of Business Management, 2020)
The current business environment is considered to be unstable, uncertain, complex, andambiguous. Transformation is no longer a choice but a necessity. Lean, which is an operationsmanagement concept, has been widely adopted including to accounting. In fact, if the businessdoes not prepare for proper implementation, all the benefits cannot be obtained. Organizationalculture has been found to be very important in shaping the success of business. However, atraditional organizational culture is also not capable of sustaining the long-term success of leanaccounting. Increased income, cost avoidance, and time and cost efficiency were obtained fromlean accounting success implementation. The most important thing is that a supportiveorganizational culture can make lean implementation deeper, into a mindset and reflected in theactions of all people in the organization so that business entities remain adaptive in industrialchanges.